Current debates and advances in tick microbiome research - Wu-Chuang, Alejandra; Hodžić, Adnan; Mateos-Hernández, Lourdes; Estrada-Peña, Agustín; Obregon, Dasiel; Cabezas-Cruz, Alejandro (Current research in parasitology & vector-borne diseases, 2021)
The main importance of ticks resides in their ability to harbor pathogens that can be transmitted to terrestrial vertebrates including humans. Recently, studies have focused on the taxonomic and functional composition of the tick microbiome, its microbial diversity and variation under different factors including tick species, sex, and environment among others. Of special interest are the interactions between the tick, the microbiome and pathogens since tick microbiome can influence pathogen colonization within the tick vector, and potentially, transmission to the vertebrate host. In this review, we tackled a synthesis on the growing field of tick microbiomes. We focus on the current state of tick microbiome research, addressing controversial and hotly debated topics and advances in the precise manipulation of tick microbiome. Furthermore, we discuss the innovative anti-tick microbiota vaccines as a possible tool for microbiome modulation and thus, control of tick-borne diseases. Deciphering tick-microbiome pathogen interactions can spur new strategies to control tick-borne diseases via modulation of tick microbiome. [Display omitted] •Whether the diversity observed in tick microbiomes concerns the biology or the methodology remains an open question.•Tick immunity must play a major role in selecting ‘who stays and who leaves’ the microbiome.•Anti-tick microbiota vaccines can target specific bacteria and subsequently modulate tick microbiome.